HUBUNGAN PENDIDIKAN, KEBIASAAN OLAHRAGA, DAN POLA MAKAN DENGAN KUALITAS HIDUP LANSIA DI PUSKESMAS WONOKROMO SURABAYA - Aviana Gita Lara; Atik Choirul Hidajah (Universitas Airlangga, 2016)
Diabetes mellitus (DM) type 2 is one of the Non Comunicable Disease (NCDs) whoseprevalence continue to increase. Riskesdas 2013 indicate an increasing in the prevalence of type 2diabetes in the elderly, namely from the year 2007 increased by 3,7% to 4,8% in 2013. SUSENAS 2014showed morbidity rate in the elderly in 2014 reached 25,05%. The increasing age of elderly make elderlysuff ered a setback in many ways, which aff ects the quality of life of the elderly. Type 2 diabetes in theelderly if not keep glucose levels either by exercise will cause complications. One of the complications oftype 2 diabetes mellitus is a microvascular complications. This study aimed to analyze the relationshipbetween exercise habits and symptoms of microvascular complications with quality of life of elderlypatients with type 2 DM in Puskesmas Wonokromo. This type of research is observational analytic studywith sample of elderly patients with DM 2 who was treated at the Puskesmas Wonokromo as many as96 samples. The technique sampling was Simple Random Sampling. The data analysis used Chi SquareTest. The results showed no corrrelations between education and diet with quality of life, theres was acorrrelations exercise habits and quality of life (p = 0.005). Expected that elderly patients with type 2diabetes were can improve the quality of life with regular exercise.Keywords: T2 Diabetes mellitus, Quality of life, Elderly